Upaya Peningkatan Output Produksi Pada Fasilitas Kerja Departemen Preparation Di PT. Integra Indocabinet - Lim Robby Jayadi; Herry Christian Palit (Jurnal Titra, 2015)
PT. Integra Indocabinet is a company which produces indoor furniture that is make to order. Problems were discovered on the production floor of Preparation Department, they are in the process of jumping saw and the rotary press. Problem that occurred in the process of jumping saw was inefficient of unloading activities then resulting in the accumulation of wood. On the other hand, problem that occurred in the process of rotary press was overtime process. Regarding of those problems, proposed improvement was given to jumping saw process by redesign its table in order to be more efficient then can speed up the unloading time. While for the rotary press process, it was proposed to add glue spreader roll on each rotary machine so that the clamping process would approach the ideal processing time. Trial of improved jumping saw process has been done and has proven to increase production capacity by 34%, but for the rotary press has not been done yet due to unavailability of spreader roll and unfinished of re-layout process.